Westering women : a novel - Dallas, Sandra (St. Martin's Press, 2020)
"From the bestselling author of Prayers for Sale, an inspiring celebration of sisterhood on the perilous Overland Trail. "If you are an adventuresome young woman of high moral character and fine health, are you willing to travel to California in search of a good husband?" It's February, 1852, and all around Chicago, Maggie sees the postings soliciting "eligible women" to travel to the gold mines of Goosetown. A young seamstress with a small daughter and several painful secrets, she has nothing to lose. So she joins forty-three other women and two pious reverends on the dangerous 2,000-mile journey west. None of them are prepared for the hardships they face on the trek through the high plains, mountains, and deserts, or for the triumphs of finding strengths they did not know they possessed. And not all will make it. As Maggie gets to know the other women, she soon discovers that she's not the only one looking to leave dark secrets behind. And when her past catches up with her, it becomes clear a band of sisters will do whatever it takes to protect one of their own"--